Is downloading articles through “shortcuts” reasonable? study of normative perceptions of accounting students - Kamil, Irham; Asih, Putri Nuril Wulanatining; Cita, Widya (Universitas Muhammadiyah Malang, 2025)
Purpose: This study aims to analyze and change the normative perceptions of accounting students regarding the behaviour of downloading articles using Sci-Hub with message framing. Methodology/approach: The method used in this research is distributing questionnaires to accounting students in Malang and testing using non-parametric differential tests. Findings: The results of this study indicate that students consider downloading articles using Sci-Hub a natural thing. Framing containing negative messages is more effective in changing the attitude of Sci-Hub users to be wiser and aware of unethical behaviour. Practical implications: This research has implications for academics and universities to continuously provide anti-journal piracy messages to students. Originality/value: Given the lack of consensus in the findings, this research is focus on framing effects.